Submodules of secondary modules - Shahabaddin Ebrahimi Atani (International Journal of Mathematics and Mathematical Sciences)
Let R be a commutative ring with nonzero identity. Our objective is to investigate representable modules and to examine in particular when submodules of such modules are representable. Moreover, we establish a connection between the secondary modules and the pure-injective, the Σ-pure-injective, and the prime modules.